ANALYSIS OF CHILDREN'S FRIENDLY SCHOOL POLICY IMPLEMENTATION IN SMP NEGERI 6 DEPOK - Rangkuti, Safitri Ridwan; Maksum, Irfan Ridwan (JPSI (Journal of Public Sector Innovations), 2019)
Child-friendly and child-based schools are an effort to fulfill children's rights and provide quality education for children. This study aims to explain the implementation of Child Friendly School Policies established by the Ministry of Women's Empowerment and Child Protection and analyze the supporting and inhibiting factors for the implementation of Child Friendly School Policies in SMP Negeri 6 Depok. This study used a qualitative method that shows the implementation of the Child Friendly School Policy in SMPN 6 Depok been going well, assessed in the context of the process, results (output), impact (outcomes) and causality (causal connection).The factors that support the implementation of the Child Friendly School Policy at SMP Negeri 6 Depok are good and smooth communication, attitudes and commitment of all school people, coordination between the Depok Government and the School and the positive support of all school members, parents, surrounding communities. However, there are still obstacles, namely the limited school budget and the number of teachers, and the density of teacher activities that have caused the implementation of policies to be not optimal.